DLX2 promotes gastric cancer epithelial– mesenchymal transition and malignant progression through the PI3K/AKT signaling pathway - Chen, Wenjing; Chen, Xietao; Chi, Xuanfu; Yu, Wenpiao; Jin, Jinji; Cheng, Jun (Frontiers in Oncology, 2025)
IntroductionGastric cancer (GC) is a major health challenge globally, with poor outcomes often due to late-stage diagnosis and aggressive tumor behavior. This study examines the role of DLX2 in GC progression, focusing on its activation of the PI3K/AKT pathway and induction of EMT, which promote tumor cell proliferation, migration, and anchorage-independent growth. We hypothesize that DLX2 is an independent prognostic marker and modulates the tumor immune microenvironment.MethodsTCGA RNA sequencing data was analyzed to assess DLX2 as a prognostic factor. In vitro experiments with cell transfection and Western blotting confirmed the effects of DLX2 on EMT and the PI3K/AKT pathway. Functional assays and in vivo models evaluated the impact of DLX2 on tumor cell migration, invasion, and growth. Immune scoring analysis explored the relationship between DLX2 and the tumor immune microenvironment.ResultsHigh DLX2 expression correlated with reduced survival rates. In vitro and in vivo studies showed that DLX2 overexpression enhanced EMT, activated the PI3K/AKT pathway, and increased tumor cell migration and invasion. Immune scoring analysis indicated a significant association between DLX2 expression and immune/stromal scores.DiscussionDLX2 emerges as a key regulator in GC malignancy and a potential therapeutic target. Its association with the tumor immune microenvironment suggests a role in GC treatment. Future research should explore DLX2-targeted therapies to enhance GC patient outcomes, offering a promising direction for precision oncology.